To Treat or to Wait? - I.V. Bogadelnikov; L.I. Prokudina; Ye.V. Zdyrko; Yu.V. Vyaltseva (Zaslavsky O.Yu., 2012)
Infectious reasons of central nervous functions dysfunction are most aggressive, as they cause aggravation of neurological deficit. It requires the immediate specific therapy.